The Police and guards in the Abbasid era - Al-Naqarsh, Ismail Hassan Mustafa (Journal of Humanities & Social Sciences, 2019)
The aim of the study was to know the origins and development of the police and guard institution in the Abbasid era as one of the important administrative institutions in the Islamic State. The concept of the police dealt with language and terminology and dealt with the characteristics that must be met by the police officer. Also, it dealt with the Means and methods followed by the institution in the implementation of its objectives in addition to the weapons and means, the means of transportation used. The study concluded to identify the numbers and ranks of the members of the institution and their data.
Keywords: Police; Guard; Abbasid era; Islamic era